2012
DOI: 10.1134/s106816201202015x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of sea anemone Heteractis crispa Kunitz type polypeptides with pain vanilloid receptor TRPV1: In silico investigation

Abstract: Using methods of molecular biology we defined the structures of the 31 sea anemone Heteractis crispa genes encoding polypeptides which are structurally homologous to the Kunitz proteinase inhibitor family. Identified amino acid sequences have point residue substitutions, high degree of homology with sequences of known H. crispa Kunitz family members, and represent a combinatorial library of polypeptides. We generated their three-dimensional structures by homologous modeling methods. Analysis of their molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…However, one unique peptide, HCRG21, has Thr14 at this position, similar to the representatives of so named “analgesic cluster” of HCGS peptide subfamily have. This cluster is composed of analgesic peptides APHC1–APHC3 which are also known as modulators of the TRPV1 receptor [28,30,31,32]. HCRG21 shares 82% to 95% of identity with APHC1–APHC3, as well as with Jn-IV, InhVJ, and some HCGS peptides deduced by the PCR-based cloning technique (HCGS1.10, HCGS1.34, HCGS1.36, HCGS1.26, and HCGS2.3) (Figure 1a) [11].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, one unique peptide, HCRG21, has Thr14 at this position, similar to the representatives of so named “analgesic cluster” of HCGS peptide subfamily have. This cluster is composed of analgesic peptides APHC1–APHC3 which are also known as modulators of the TRPV1 receptor [28,30,31,32]. HCRG21 shares 82% to 95% of identity with APHC1–APHC3, as well as with Jn-IV, InhVJ, and some HCGS peptides deduced by the PCR-based cloning technique (HCGS1.10, HCGS1.34, HCGS1.36, HCGS1.26, and HCGS2.3) (Figure 1a) [11].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, on the basis of experimental data [28] and computer modeling [32], it was suggested that the most functionally important residues are Glu6, Thr14, Val31, Glu38, Arg48, and Arg51 in APHC1. All these residues are conserved between APHC1 and HCRG21, except Val31, which is replaced by a Pro in HCRG21.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations